Conceptual overview of the Olifants River Basin's groundwater, South Africa. Occasional paper - Aston, J.J. (International Water Management Institute, 2000)
This paper, commissioned by the International Water Management Institute (IWMI), presents an overview of the state of knowledge of groundwater issues in the Olifants River Basin in South Africa. It traces work, completed or ongoing, that has a direct or circumstantial relevance to the Olifants River Basin and presents a summary of the known state of existence of groundwater in the basin. The paper examines both the physical presence of the underground water and, though to a lesser extent, the social exploitation of this resource. The examination of the availability of groundwater will include a general description of the aquifer types, the recharge of water to these host aquifers and the flow of groundwater through and availability for extraction from the aquifers. The study goes on to look at the quality of this water, its present use, and the extent to which there are institutional bodies managing this water. By the end of this paper the reader should have a broad overview of the extent of the importance of this valuable natural resource to the development of the Olifants river basin together with an insight into the future potential to more fully yet sustainably utilise this resource. Overall the structure and content of the paper has been kept to a level that gives a good introduction to some of the themes relevant to the basin's groundwater reserve and acts as a platform from which to successfully manage future work.